2013
DOI: 10.4103/2249-4863.109939
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of chikungunya in southern Odisha

Abstract: Background:The emergence of chikungunya (CHIK) infection was observed in Odisha, India in 2006. Thereafter many cases with symptoms suggestive of CHIK were reported from different districts of Southern-Odisha. This study was aimed to know the seroprevalence, clinical presentations and seasonal trends of CHIK infection in this region.Materials and Methods:This study was conducted in a tertiary hospital of this region. Serum samples received in the Department of Microbiology from various districts of Southern-Od… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
16
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 10 publications
(16 reference statements)
10
16
3
Order By: Relevance
“…It was observed in this study that the age group ≤60 years of age were found to be more susceptible to CHIKV infection which is in consonance with previous reports (Mohanty et al, 2013;Patil et al, 2013). This is the most active age group and coupled with movement of people outdoors during the day time when the activity of A. albopictus is at its peak, lesser personal protection and individual difference in immune response to diseases are some of the speculative reasons for increased susceptibility to CHIKV infection in this age group.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…It was observed in this study that the age group ≤60 years of age were found to be more susceptible to CHIKV infection which is in consonance with previous reports (Mohanty et al, 2013;Patil et al, 2013). This is the most active age group and coupled with movement of people outdoors during the day time when the activity of A. albopictus is at its peak, lesser personal protection and individual difference in immune response to diseases are some of the speculative reasons for increased susceptibility to CHIKV infection in this age group.…”
Section: Discussionsupporting
confidence: 81%
“…This could be attributed to the increased vector abundance and activity during rainy season as observed in study and in previous investigations (Mavalankar et al, 2008;Suryawanshi et al, 2009;Balasubramaniam et al, 2011;Dwibed et al, 2011;Mohanty et al, 2013). The patients in the present study that exhibited fever and headache were observed to show the highest prevalence of CHIKV antibody which could be the major symptoms of CHIKV infection in this environment.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…The acute phase lasts for 2-3 days and may remit for 1-2 days after a gap of 4-10 days resulting in a "saddle back" fever curve (Mohanty et al, 2013). Most infections completely resolve within weeks but there are reported cases of CHIK V induced arthralgia lasting for months or even for years in the form of recurrent or persistent episodes (Narayan Shrihari et al, 2012).…”
Section: Introductionmentioning
confidence: 99%